2017
DOI: 10.1093/mnras/stx899
|View full text |Cite
|
Sign up to set email alerts
|

The inner structure of early-type galaxies in the Illustris simulation

Abstract: Early-type galaxies provide unique tests for the predictions of the cold dark matter cosmology and the baryonic physics assumptions entering models for galaxy formation. In this work, we use the Illustris simulation to study correlations of three main properties of early-type galaxies, namely, the stellar orbital anisotropies, the central dark matter fractions and the central radial density slopes, as well as their redshift evolution since z = 1.0. We find that lower-mass galaxies or galaxies at higher redshif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
144
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(172 citation statements)
references
References 95 publications
(201 reference statements)
28
144
0
Order By: Relevance
“…The total power-law slope also correlates with the in-situ formed stellar mass ratio and redshift, in line with previous simulation studies (Xu et al 2017;Remus et al 2017;Bellstedt et al 2018). Although a slightly negative total density slope/central velocity dispersion correlation and a shallower slope with time are in tension with observational trends, the uncertainties and systematics in observations may have obscured the true trends (Xu et al 2016(Xu et al , 2017Tagore et al 2018). In this work, we will hence investigate the redshift evolution of the density profiles of z = 0 ETG progenitors, and statistical ETG samples at higher redshifts selected based on their morphology.…”
Section: Introductionsupporting
confidence: 90%
See 3 more Smart Citations
“…The total power-law slope also correlates with the in-situ formed stellar mass ratio and redshift, in line with previous simulation studies (Xu et al 2017;Remus et al 2017;Bellstedt et al 2018). Although a slightly negative total density slope/central velocity dispersion correlation and a shallower slope with time are in tension with observational trends, the uncertainties and systematics in observations may have obscured the true trends (Xu et al 2016(Xu et al , 2017Tagore et al 2018). In this work, we will hence investigate the redshift evolution of the density profiles of z = 0 ETG progenitors, and statistical ETG samples at higher redshifts selected based on their morphology.…”
Section: Introductionsupporting
confidence: 90%
“…These galaxies show correlations between the total power-law slope with galaxy size, stellar mass, surface density and central dark matter fraction that are broadly consistent with both local and distant observations. The total power-law slope also correlates with the in-situ formed stellar mass ratio and redshift, in line with previous simulation studies (Xu et al 2017;Remus et al 2017;Bellstedt et al 2018). Although a slightly negative total density slope/central velocity dispersion correlation and a shallower slope with time are in tension with observational trends, the uncertainties and systematics in observations may have obscured the true trends (Xu et al 2016(Xu et al , 2017Tagore et al 2018).…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…Tortora et al 2014a;Poci et al 2017) and at high redshifts, where gas and in situ star formation dominate the galaxy evolution, the ETGs from cosmological simulations have a total density slope very steep (α ∼ −3), with merging events driving the galaxy to a nearly isothermal profile (Remus et al 2013(Remus et al , 2017. Xu et al (2017) from the Illustris simulation find a that α is constant with redshift, which would leave the trend unaffected. While, using strong lenses, Bolton et al (2012) and Sonnenfeld et al (2013) have shown that the total mass density slope is steeper at lower redshift.…”
Section: Systematicsmentioning
confidence: 98%